A New Way of Producing Isomalto-Oligosaccharide Syrup by Using the Transglycosylation Reaction of Neopullulanase - Kuriki, Takashi (1993)
A new way of producing isomalto-oligosaccharide syrup from starch was developed. Isomalto-oligosaccharides contain one or more α-(1→6)-glucosidic linkages with or without α-(1→4)-glucosidic linkages. The isomalto-oligosaccharide syrups are receiving increased attention as food additives because it is thought that they help prevent dental caries and improve human intestinal microflora, acting as a growth factor for bifidobacteria. The new system for production of isomalto-oligosaccharide syrup is based on the strong α-(1→6)-transglycosylation reaction of neopullulanase. Bacillus subtilis saccharifying α-amylase was simultaneously used with neopullulanase to improve the yield of isomalto-oligosaccharides. The yield of isomalto-oligosaccharides was increased to more than 60%, compared with a yield of 45.0% obtained by the conventional system. To reduce the costs, the use of immobilized neopullulanase was investigated. Almost the same yield of isomalto-oligosaccharides was obtained by using immobilized neopullulanase.